Too little but not too late: Results of a literature review to improve routine immunization programs in developing countries - Cairns K Lisa; Dietz Vance; Ryman Tove K (BMC, 2008)
Abstract Background Globally, immunization services have been the center of renewed interest with increased funding to improve services, acceleration of the introduction of new vaccines, and the development of a health systems approach to improve vaccine delivery. Much of the credit for the increased attention is due to the work of the GAVI Alliance and to new funding streams. If routine immunization programs are to take full advantage of the newly available resources, managers need to understand the range of proven strategies and approaches to deliver vaccines to reduce the incidence of diseases. In this paper, we present strategies that may be used at the sub-national level to improve routine immunization programs. Methods We conducted a systematic review of studies and projects reported in the published and gray literature. Each paper that met our inclusion criteria was rated based on methodological rigor and data were systematically abstracted. Routine-immunization - specific papers with a methodological rigor rating of greater than 60% and with conclusive results were reported. Results Greater than 11,000 papers were identified, of which 60 met our inclusion criteria and 25 papers were reported. Papers were grouped into four strategy approaches: bringing immunizations closer to communities (n = 11), using information dissemination to increase demand for vaccination (n = 3), changing practices in fixed sites (n = 4), and using innovative management practices (n = 7). Conclusion Immunization programs are at a historical crossroads in terms of developing new funding streams, introducing new vaccines, and responding to the global interest in the health systems approach to improving immunization delivery. However, to complement this, actual service delivery needs to be strengthened and program managers must be aware of proven strategies. Much was learned from the 25 papers, such as the use of non-health workers to provide numerous services at the community level. However it was startling to see how few papers were identified and in particular how few were of strong scientific quality. Further well-designed and well-conducted scientific research is warranted. Proposed areas of additional research include integration of additional services with immunization delivery, collaboration of immunization programs with new partners, best approaches to new vaccine introduction, and how to improve service delivery.